280 упростите выражение 1) (x²-1)3x-(x²-2)2x 2) (4a²-3b)2b-(3a²-4b)3b
3) 2(3a+4)+3(a-7)-7(2a-7)
4) 3(2x-1)-5(x-3)+6(3x-4)


Dasha57891 Dasha57891    1   17.12.2020 20:20    0

Ответы
allagureva allagureva  16.01.2021 20:22

Пошаговое объяснение:

1) =3х^3-3х-2х^3+4х=х^3+х=x(x^2+1)

2) =8a^2b-6b^2-9a^2b+12b^2=

= - a^2b+6b^2=b(-a^2+6b)

3) =6a+8+3a-21-14a+49= - 5a+36

4) =6x-3-5x+15+18x-24=19x-12

ПОКАЗАТЬ ОТВЕТЫ
Елизбабак Елизбабак  16.01.2021 20:22

1)=3x^ ^ 3-3x-2x^ ^ 3+4x=x^ ^ 3+x=x(x^ ^ 2+1)

2)=8a^ ^ 2b-6b^ ^ 2-9a^ ^ 2b+12b^ ^ 2= =-a^ ^ 2b+6b^ ^ 2=b(-a^ ^ 2+6b) 3)=6a+8+3a-21-14a+49=-5a+36 4)=6x-3-5x+15+18x-24=19x-12

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика